The antioxidant properties of the medicinal fruits: a pivotal mechanism of their nutritional, pharmacological, and cardioprotective effects - Yuan, Shi-Min; Song, Xiu-Qin (Progress in Nutrition, 2019)
Background and Purpose: The pharmacological properties of the medicinal fruits are insufficiently elucidated and the mechanisms remain to be clarified. The purpose of this article is to describe the antioxidant properties of the medicinal fruits. Materials and Methods: Pertinent literature of the medicinal fruits, Lycium barbarum, mulberry, kiwifruit, and avocado were comprehensively screened for analysis. Results: The medicinal fruits are also rich in antioxidative components, especially the phenolic ingredients, with significant antioxidant capacities in addition to the nutrients contained. By decreasing the reactive oxygen species and promoting the levels of superoxide dismutase, catalase, and glutathione peroxidase, they play an important protective effect against deoxyribonucleic acid damage and myocardial, hepatic, and other organ damages. Based on the antioxidant mechanism, modifying the storage conditions with low O2 and low temperature may prevent fruit ripening and control lipid oxidation. Conclusions: The medicinal fruits are not only nutritious foods, but also healthcare and medical agents as well. The underlying mechanisms responsible for the protective effects are via antioxidative properties.